Multicentre randomised double-blinded placebo-controlled trial of favipiravir in adults with mild COVID-19 - Bosaeed, Mohammad (BMJ Open, 2021)
INTRODUCTION: A novel coronavirus, designated SARS-CoV-2, caused an international outbreak of a respiratory illness, termed COVID-19 in December 2019. There is a lack of specific therapeutic agents based on evidence for this novel coronavirus infection; however, several medications have been evaluated as a potential therapy. Therapy is required to treat symptomatic patients and decrease the virus carriage duration to limit the communitytransmission. METHODS AND ANALYSIS: We hypothesise that patients with mild COVID-19 treated with favipiravir will have a shorter duration of time to virus clearance than the control group. The primary outcome is to evaluate the effect of favipiravir on the timing of the PCR test conversion from positive to negative within 15 days after starting the medicine. Adults (>18 years, men or nonpregnant women, diagnosed with mild COVID-19 within 5 days of disease onset) are being recruited by physicians participating from the Ministry of National Guard Health Affairs and the Ministry of Health ethics committee approved primary healthcare centres. This double-blind, randomised trial comprises three significant parts: screening, treatment and a follow-up period. The treating physician and patients are blinded. Eligible participants are randomised in a 1:1 ratio to either the therapy group (favipiravir) or a control group (placebo) with 1800 mg by mouth two times per day for the first day, followed by 800 mg two times per day for 4–7 days. Serial nasopharyngeal/oropharyngeal swab samples are obtained on day 1 (5 days before therapy). On day5±1 day, 10±1 day, 15±2 days, extra nasopharyngeal/oropharyngeal PCR COVID-19 samples are requested. The primary analysis population for evaluating both the efficacy and safety outcomes will be a modified intention to treat population. Anticipating a 10% dropout rate, we expect to recruit 288 subjects per arm. The results assume that the hazard ratio is constant throughout the study and that the Cox proportional hazard regression is used to analyse the data. ETHICS AND DISSEMINATION: The study was approved by the King Abdullah International Medical Research Centre Institutional Review Board (28 April 2020) and the Ministry of Health Institutional Review Board (1 July 2020). Protocol details and any amendments will be reported to https://clinicaltrials.gov/ct2/show/NCT04464408. The results will be published in peer-reviewed journals. TRIAL REGISTRATION NUMBER: National Clinical Trial Registry (NCT04464408).